Effect of climate change on the health status of children in South West Nigeria (2015)
Children' represent a particularly vulnerable group drat is likely to suffer disproportionately from both direct and indirect adverse health effects of climate change. Conservative environmental estimates of die impact of climate change that are already in process indicate that they-will result in numerous health effects to children. The study examined the effect of climate change on die health status of-children in Southwest Nigeria. One; hundred and twenty medical practitioners and two hundred and sixty parents of affected children were randomly sampled from ten health facilities in Oyo, Ogun, Osun and Lagos States Data were collected through interview schedule and structured questionnaire. The data were analysed using descriptive statistics and Pearson Product Moment Correlation at p < .0.05 level of significance. The result of die study indicated that 53.0% of die severely affected children are boys .and a significant relationship between climate change on gender (r-0.228, p-0.022 α-0.05). There was no significant relationship between age and climate change. More than half of die parents (87.0%). do not have access to adequate information on die negative effect of climate change on their children It was recommended that adaptation agenda that focuses on die realities of children’s health be pursued vigorously from die homes to die Federal government levels. Parents should be educated through print and electronic media on die need to plant trees to combat die effect of die ozone layers depletion.